2022
DOI: 10.3389/fphys.2022.897105
|View full text |Cite
|
Sign up to set email alerts
|

The Chemerin-CMKLR1 Axis is Functionally important for Central Regulation of Energy Homeostasis

Abstract: Chemerin is an adipokine involved in inflammation, adipogenesis, angiogenesis and energy metabolism, and has been hypothesized as a link between obesity and type II diabetes. In humans affected by obesity, chemerin gene expression in peripheral tissues and circulating levels are elevated. In mice, plasma levels of chemerin are upregulated by high-fat feeding and gain and loss of function studies show an association of chemerin with body weight, food intake and glucose homeostasis. Therefore, chemerin is an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…Photoperiodicity also affects chemerin expression in the rat hypothalamus where long days increase chemerin expression compared to short days, suggesting that this could influence energy balance and body weight [ 64 ]. This has been confirmed in rat experiments in which a shRNA that reduces chem1 mRNA was injected into the arcuate nucleus of the hypothalamus in rats, resulting in acute weight loss and the chronic inhibition of weight gain [ 65 ]. These data suggest that chemerin via chem1 exerts its effects on energy homeostasis via central regulation as well as in the periphery [ 66 , 67 ].…”
Section: Chemerin Expression and Activity In Cells And Tissuesmentioning
confidence: 87%
“…Photoperiodicity also affects chemerin expression in the rat hypothalamus where long days increase chemerin expression compared to short days, suggesting that this could influence energy balance and body weight [ 64 ]. This has been confirmed in rat experiments in which a shRNA that reduces chem1 mRNA was injected into the arcuate nucleus of the hypothalamus in rats, resulting in acute weight loss and the chronic inhibition of weight gain [ 65 ]. These data suggest that chemerin via chem1 exerts its effects on energy homeostasis via central regulation as well as in the periphery [ 66 , 67 ].…”
Section: Chemerin Expression and Activity In Cells And Tissuesmentioning
confidence: 87%
“…15 While it is still debated how chemerin controls insulin sensitivity and glucose homeostasis through its receptors. 16 In our previous research, DsbA-L protein expression was found to be moderately upregulated with raised chemerin concentration. 17 Nevertheless, it is unclear how chemerin interacts with DsbA-L and whether chemerin has any influence on the cGAS-STING pathway.…”
Section: Introductionmentioning
confidence: 84%
“…Adipokine chemerin, encoded by retinoic acid receptor responder 2 ( RARRES2 ) gene, is also a multifaceted biomolecule which is involved in GDM 15 . While it is still debated how chemerin controls insulin sensitivity and glucose homeostasis through its receptors 16 . In our previous research, DsbA‐L protein expression was found to be moderately upregulated with raised chemerin concentration 17 .…”
Section: Introductionmentioning
confidence: 91%
“…Chemokine-like receptor 1 ( CMKLR1 ) is a G-protein-coupled receptor that is mainly expressed in white adipose tissue and immune cells such as microglia, macrophages, and dendritic cells [ 390 ]. CMKLR1 interacts with endogenous ligands such as the adipokine Chemerin, and helps to modulate metabolic processes and cell proliferation, especially during glucose processing, adipogenesis, and angiogenesis [ 390 ].…”
Section: Genetic Variants Affecting Microglial Response To Aβmentioning
confidence: 99%
“…Chemokine-like receptor 1 ( CMKLR1 ) is a G-protein-coupled receptor that is mainly expressed in white adipose tissue and immune cells such as microglia, macrophages, and dendritic cells [ 390 ]. CMKLR1 interacts with endogenous ligands such as the adipokine Chemerin, and helps to modulate metabolic processes and cell proliferation, especially during glucose processing, adipogenesis, and angiogenesis [ 390 ]. In immune cells, CMKLR1 induces chemotaxis and pro-inflammatory cascades, but is also involved in anti-inflammatory signaling through interactions with pro-resolving ligands such as Resolvin E1 [ 391 ].…”
Section: Genetic Variants Affecting Microglial Response To Aβmentioning
confidence: 99%